E-CATALOGUE POLA PERJALANAN WISATA BAHARI DI KAWASAN WISATA PULAU PISANG DAN LABUHAN JUKUNG, KABUPATEN PESISIR BARAT, PROVINSI LAMPUNG - Larisa Nabila Putri; Deddy Sobarna Sutadji; Eko Susanto (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2019)
The research is based on information services that affect the popularity of the Pulau Pisang and Labuhan Jukung Tourism Areas in the Pesisir Barat Regency, Lampung Province. This area has high tourism potential in the form of islands, beaches, and sea. Information services are an important factor in tourism to attract tourist visits. This study aims to determine digital information technology in the form of an e-catalog that includes marine tourism information in the form of a map and a description of the information therein. The E-catalog for Marine Tourism in the Pulau Pisang and Labuhan Jukung areas can support travel agencies in arranging marine thematic tour packages. The descriptive-qualitative research method is applied by using observation data techniques, interviews, and documentation studies of the research object. The focus of the design is on marine tourism activities in the Pulau Pisang and Labuhan Jukung Tourism Areas, namely beach volleyball, swimming, sunbathing, fishing, snorkeling, diving, boating, and surfing, as well as tourism supporting components, namely amenities, accessibility and support services. There are also two forms of travel patterns that are reviewed for tourists, namely through the start and end points of the journey from the same route, or a continuous path with the end point of the trip by visiting new destinations on different routes.